Interpretation of Santri Salaf From Islamic Boarding School (Pesantren) National Narratives - Khoirul Mustamir, Ahmad (Program Studi Pendidikan Agama Islam (PAI), 2023)
Muslims are under pressure to elaborate rationales for their growing sense of nationalism within the context of the pesantren community. The three-volume National Jurisprudence Book was created by Pesantren Lirboyo in response to this occurrence. The researcher adopted a qualitative hermeneutic viewpoint to better understand the pesantren community's patriotic ideals. In-depth interviews with long-term validity checks, document analyses, and meeting observations are the data sources. While the developed analysis criticizes Antonio Gramsci's ideological hegemony's underpinnings. The results of the investigation indicated that problem-solving efforts employ the yellow book study method and contemporary legal studies (contactability). Thus, fiqh can acquire a broader (contextual) meaning without excluding fundamental values such as patriotism from the realm of faith. In conclusion, Pesantren Ma'had Aly Lirboyo contributes to the formulation of Fiqh Kabangsaan values recognizing the existence of the Indonesian nation. In this manner, the community of Pondok Lirboyo opposes all movements that reject Pancasila as the foundation of the Unitary State of the Republic of Indonesia.